Morphological, molecular and pathogenic characterization of Rhizoctonia isolates causing a banded spot of corn sheath in northern Sinaloa - Rabago-Zavala, Karen (2025)
Corn production is affected by fungi of the genus Rhizoctonia. The objective of this study was to characterize, using morphology, DNA sequence analysis, and pathogenicity, Rhizoctonia isolates associated with corn with banded leaf spot symptoms in commercial fields in northern Sinaloa. Diseased plants were collected in the municipalities of Ahome, El Fuerte, and Guasave, obtaining 27 isolates. Morphological characterization on PDA showed colonies with whitish to brown mycelium, pigment release into the medium, and amorphous, red and brown sclerotia with a diameter < 1 mm, characteristics described for Rhizoctonia. For molecular characterization, genomic DNA was extracted, part of the RPB2 gene was amplified by PCR, and the amplified products were sequenced. Phylogenetic analysis confirmed the identification of 18 isolates as Rhizoctonia zeae and 9 isolates as Rhizoctonia solani. The R. solani isolates correspond to the anastomosis group (AG): AG-4. Three of them correspond to the anastomosis subgroup AG-4 HGI and the other 6 to the subgroup AG-4 HGIII. The pathogenicity and severity of the isolates were evaluated in corn plants 34 days after planting, revealing significant differences (p > 0.05). This study will allow the development of disease management strategies and future research into biological and chemical control of Rhizoctonia species.